Streptomycin Resistance in a Streptomycin-Producing Microorganism - Piwowarski, Janet M. (1979)
Cell-free extracts of Streptomyces bikiniensis contain an adenosine 5′-triphosphate-dependent kinase which inactivates streptomycin (Sm) and dihydrostreptomycin by phosphorylation. The products have been identified as streptomycin 6-phosphate and dihydrostreptomycin 6-phosphate. Activity was not present in logarithmic-phase cells, which were susceptible to 25 μg of Sm per ml. In stationary-phase cells, activity appeared 12 h before detectable Sm in the medium. These cells were resistant to more than 200 μg of Sm per ml. Certain S. bikiniensis isolates selected from cultures treated with acriflavine or ethidium bromide lost the ability to produce Sm and became susceptible to 10 μg of Sm per ml throughout their growth. Cell-free extracts of the dye-treated isolates did not inactivate Sm and lacked streptomycin kinase activity at all stages in development. Ribosomes from resistant cells bound the same amount of [(3)H]dihydrostreptomycin as ribosomes from susceptible cells, and there was no correlation between the uptake of [(3)H]dihydrostreptomycin and resistance. The Sm-inactivating enzyme was identified as streptomycin-6-kinase. These results suggest that phosphorylation by streptomycin-6-kinase is a major factor in resistance in S. bikiniensis.